Iterative technique and finite element simulation for supplemental condition monitoring of water-tube boiler - Purbolaksono J.; Khinani A.; Ali A.A.; Rashid A.Z.; Nordin N.F. (2023)
Process of monitoring a parameter of condition in heat recovery steam generator (HRSG) system is particularly important. In this paper a new supplemental method for condition monitoring of water-tube boiler (superheater and reheater) through iterative technique and finite element simulation is proposed. The method is utilizing the empirical formula for estimating scale thickness developed on the inner surface of the tube over period of time. An iterative procedure is carried out to determine the average temperature in the tube as scale thickness on the inner surface increases. Different heat transfer parameters governing the problem are used and evaluated. The results obtained by using the proposed method are verified with the actual data of the available reports. Examples on failure analysis of the boiler tube utilizing the proposed technique are presented. The method may provide better estimation, provided that all the heat transfer parameters are well specified by the HRSG operators. 2009 Elsevier B.V. All rights reserved.